Current update on surgical management for spinal tuberculosis: a scientific mapping of worldwide publications - Romaniyanto, Romaniyanto; Ilyas, Muhana Fawwazy; Lado, Aldebaran; Sadewa, Daffa; Dzikri, Dykall Naf'an; Budiono, Enrico Ananda (Frontiers in Surgery, 2025)
IntroductionSpinal tuberculosis (TB), or Pott's disease, remains a significant global health issue, particularly in regions with high TB prevalence. Despite antitubercular drug therapy being the primary treatment, surgical intervention is often required in cases of spinal instability or neurological complications. This study aims to conduct a comprehensive bibliometric analysis of worldwide publications related to the surgical management of spinal TB and to compare contributions from orthopaedic surgery and neurosurgery in this field.MethodsA bibliometric analysis was performed using data from the Scopus database, covering publications from 1896 to 2024. The search strategy focused on terms related to spinal TB and surgical interventions. The analysis included 1,857 publications, which were examined for trends, key contributors, and the evolution of surgical techniques. Metrics such as the number of publications, leading authors, affiliations, countries, and funding sponsors were compared between orthopaedic surgery and neurosurgery.ResultsThis study identified a steady increase in the number of publications over time. Key topics evolved from basic surgical methods, including early spinal procedures, to integrating pharmacological approaches alongside surgical techniques, such as antitubercular drugs, advancing into imaging research and procedure research involving refined surgical methods like spinal fusion. The recent phase reflects a shift towards technology-driven approaches, including minimally invasive techniques, artificial intelligence, and machine learning. China emerged as the leading country with the most contributions based on author, affiliations, funding sponsors, and countries. Last, orthopaedic surgery had more publications (274) than neurosurgery (96).DiscussionIn conclusion, spinal TB surgery has evolved significantly, with a notable shift towards advanced, technology-driven approaches. Orthopaedic surgery leads in research output compared to neurosurgery. This bibliometric analysis provides valuable insights into the global research landscape, guiding future studies in the management of spinal TB.